Transformasi Pendidikan Indonesia: Sintesis Pemikiran dan Praksis KH Ahmad Dahlan dan Ki Hajar Dewantara dalam Era Digital - Aria Ahmad Mangunwibawa; Sudarnoto Abdul Hakim; Zamah Sari (Jurnal Kajian Ilmiah, 2025)
This study aims to explore and synthesize the educational thought and praxis of KH Ahmad Dahlan and Ki Hajar Dewantara as a conceptual foundation for the transformation of Indonesian education in the digital era. Using a qualitative-philosophical approach through literature review and hermeneutic analysis, the research reveals the core values of progressive education based on faith, knowledge, and action according to KH Ahmad Dahlan, as well as holistic and humanistic education rooted in national culture according to Ki Hajar Dewantara. The findings indicate that synthesizing the thoughts of these two figures can provide a new direction for the development of an education system that integrates spiritual values, character, and technology in a balanced manner. This synthesis is relevant in addressing contemporary challenges such as digitalization, hybrid learning, artificial intelligence, and the identity crisis in national education. The study recommends an educational model grounded in both local and universal values, and adaptive to digital disruption, to shape Indonesian individuals who are independent, faithful, and globally competitive.